«Militate the Church»: youth militant careers in contemporary argentine catholicism - Fernández, Natalia Soledad (2023)
The objective of the article is to understand and analyze the contemporary youth militancies within Acción Católica Argentina (ACA), an association created in 1931 and currently active in Argentina. To do this, youth senses about catholic militancy, commitments and careers deployed by young militants are addressed. The qualitative study is based on in-depth interviews with young Catholics, participant observation in catholic sociability spaces and youth institutional sources. Among the youths, legitimate 60 forms of the military are evident in catholic spaces, reconfigurations of the meanings of the militancy category in the face of a context of youth politicization in Argentina since 2003, and youth commitments to transmit catholic values in different socio-political spheres. The study of the militancies in ACA allows us to observe an important commitment of the Church in the integral catholic formation of young militants throughout the 20th century, which is revitalized in the 21st century with the assumption of Pope Francis.